Purulent-septic complications of acute necrotizing pancreatitis: prognosis of development and early diagnosis - Rotar, O. V.; Khomiak, I. V.; Rotar, V. I.; Shafraniuk, V. D.; Hrama, O. V.; Kropyva, V. V. (Zaporozhye Medical Journal, 2020)
Aim. To determine frequency and causes of purulent-septic complications of acute necrotizing pancreatitis, to elaborate and introduce into clinical practice prognostic and early diagnostic criteria for infection of pathological foci in the pancreas. Material and methods. Prospective cohort study of 70 patients with severe acute necrotizing pancreatitis was performed in one intensive care department during the years 2015-2019. Clinical, bacteriological and instrumental examinations were carried out. Serum concentration of sCD14 receptors and presepsin were determined. Results. Overall mortality rate reached 18.8 %, but it was twice as high in patients with purulent-septic complications (P < 0.05). Primary infection of pancreatic necrotic tissues was diagnosed in 21 (55.7 %) patients. Secondary infection of pathological foci was identified in 22 (57.9 %) patients who had been operated before the 4th week and in 6 (18.6 %) – at latter periods of the disease onset. It was found that the serum content of sCD14 receptors above 1670 ng/ml at admission had been served as an independent prognostic criterion for the development of purulent-septic complications (sensitivity – 87 %, specificity – 81 %). The level of presepsin was three-four times higher in the patients with infectious complications than that in the individuals with sterile pancreatic necrosis (P < 0.01). The study showed strong correlation between presepsin concentration and infectious complications: presepsin level increased to 677 ± 30 pg/ml in patients with local purulent processes, to 988 ± 47 pg/ml – with sepsis, and to 2668 ± 583 pg/ml – with septic shock. Presepsin was the biomarker with high performance for all types of infected complications in acute necrotizing pancreatitis (ROC AUC 0.956 ± 0.007 (Р < 0.0001)). Conclusions. High level of sCD14 at admission is associated with the development of infected acute necrotizing pancreatitis. Presepsin concentration is early and highly sensitive and specific marker of purulent-septic complications in acute pancreatitis.